2015
DOI: 10.1111/papr.12301
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Framework for Mirror Therapy in Patients with Phantom Limb Pain: An Evidence‐based Practice Approach

Abstract: In this study, a structured clinical framework for the application of MT in patients with PLP was developed. This framework is currently being tested for its effectiveness in a multicenter randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 47 publications
0
29
0
1
Order By: Relevance
“…Hence, it was essential to have a decision aid based on clear criteria that enabled systematic prioritization of user requirements and ensured the identification of the most critical requirements to include as a starting point in the first prototype of the telerehabilitation platform. To this end we developed a decision matrix reflecting the views of various stakeholders based on 3 different criteria: best available evidence [9], importance of the requirement, and the technical complexity (time or money) of implementing the requirement in the platform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it was essential to have a decision aid based on clear criteria that enabled systematic prioritization of user requirements and ensured the identification of the most critical requirements to include as a starting point in the first prototype of the telerehabilitation platform. To this end we developed a decision matrix reflecting the views of various stakeholders based on 3 different criteria: best available evidence [9], importance of the requirement, and the technical complexity (time or money) of implementing the requirement in the platform.…”
Section: Discussionmentioning
confidence: 99%
“…Best available evidence: A systematic literature review regarding the clinical framework of mirror therapy for patients with phantom limb pain was conducted in a preliminary stage [9]. Literature was screened to identify studies supporting the relevance of each reported user requirement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients have described cramps when "performing voluntary phantom limb movement" (confirmed by mirror projection). Due to the risk of worsening pain, some physiotherapists prefer evolving to voluntary movements only after reaching painless movement amplitude in the phantom limb mirror projection 86,87 . This phenomenon has also been described in CRPS patients 88 .…”
Section: Phantom Limb Painmentioning
confidence: 99%
“…A common complaint among amputees is phantom limb pain (PLP), a phenomenon in which unpleasant sensations, often painful and severe, are perceived to originate from an absent limb. PLP occurs in 50%-80% of amputees, and there is no consistent evidence to support any specific pain control modality or intervention in this setting (1,(3)(4)(5)(6)(7). The objectives of this study were to (a) evaluate the safety and feasibility of …”
mentioning
confidence: 99%